Metal–Metal Synergy in Well-Defined Surface Tantalum–Iridium Heterobimetallic Catalysts for H/D Exchange Reactions - Lassalle, Sébastien; Jabbour, Ribal; Schiltz, Pauline; Berruyer, Pierrick; Todorova, Tanya K; Veyre, Laurent; Gajan, David; Lesage, Anne; Thieuleux, Chloé; Camp, Clément (Journal of the American Chemical Society, 2019)
A novel heterobimetallic tantalum/iridium hydrido complex, [{Ta(CH2 t Bu)3}{IrH2(Cp*)}] 1, featuring a very short metal–metal bond, has been isolated through an original alkane elimination route from Ta(CH t Bu)(CH2 t Bu)3 and Cp*IrH4. This molecular precursor has been used to synthesize well-defined silica-supported low-coordinate heterobimetallic hydrido species [SiOTa(CH2 t Bu)2{IrH2(Cp*)}], 5, and [SiOTa(CH2 t Bu)H{IrH2(Cp*)}], 6, using a surface organometallic chemistry (SOMC) approach. The SOMC methodology prevents undesired dimerization as encountered in solution and leading to a tetranuclear species [{Ta(CH2 t Bu)2}(Cp*IrH)]2, 4. This approach therefore allows access to unique low-coordinate species not attainable in solution. These original supported Ta/Ir species exhibit drastically enhanced catalytic performances in H/D exchange reactions with respect to (i) monometallic analogues as well as (ii) homogeneous systems. In particular, material 6 promotes the H/D exchange between fluorobenzene and C6D6 or D2 as deuterium sources with excellent productivity (TON up to 1422; TOF up to 23.3 h–1) under mild conditions (25 °C, sub-atmospheric D2 pressure) without any additives.